A method for reducing CO2 using low-temperature plasma coupled bismuth-based MOF catalyst
By using bismuth-based MOF catalyst and quartz sand in a low-temperature plasma reactor, the problems of low energy efficiency and insufficient catalytic activity of plasma conversion are solved, and efficient CO2 reduction and CO yield improvement are achieved.
Patent Information
- Application Number
- CN202310428355.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-20
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-04-20
AI Technical Summary
The prior art has low energy efficiency during plasma conversion of CO2, and the activity and selectivity of the catalyst are insufficient, making it difficult to achieve efficient reduction of CO2.
The low-temperature plasma coupled bismuth-based MOF catalyst is used to fill the Bi-MOF catalyst with quartz sand in the discharge area of the low-temperature plasma reactor, and the catalytic action of high-energy electrons in the plasma and catalysts is used to achieve the reduction of CO2.
The CO2 conversion rate and CO yield are improved, the energy density of the plasma is enhanced, the thermodynamic reaction obstacles under normal temperature and pressure are overcome, and efficient CO2 conversion under mild conditions is achieved.
Smart Images

Figure CN116588935B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a low-temperature plasma coupled bismuth-based MOF catalyst for reducing CO 2 method. Background Art
[0002] Currently, CO 2 Geological storage, fixation and chemical conversion are the key methods to collect and utilize CO 2 The main pathway is geological storage and fixation of CO 2 The cost is high and may cause potential harm to the environment, while the 2 Chemical transformation is convenient, effective and environmentally friendly, and has attracted the attention and attention of scholars around the world. 2 The chemical conversion is CO 2 Most of the carbon dioxide is converted into urea, inorganic carbonates and pigments, but only a small amount of carbon dioxide is converted into other high value-added chemicals. Among them, CO is an important chemical raw material for synthesizing organic acids, aldehydes and alcohols, which has higher added value. Therefore, CO 2 Directly converted to CO and O 2 It has attracted widespread attention. In addition, CO is also a key C1 raw material in the Fischer-Tropsch process and can be used to synthesize petroleum and oxygen-containing compounds. 2 Decomposing it into CO is a rational use of carbon resources, which is beneficial to controlling the greenhouse effect and alleviating the pressure of the global energy crisis.
[0003] Due to CO 2 The molecular structure is stable, and breaking C=O (750 kJ / mol) requires a high energy input, which is also the factor affecting CO 2 The main obstacle to effective utilization of CO 2 The traditional method of conversion is pyrolysis, but this method has high energy consumption and low energy efficiency. At high temperatures, CO and O 2 It is difficult to separate and easily cause explosion, so it is difficult to apply to large-scale industrial production. 2 However, these methods still have certain limitations, including low reaction rate, more types of by-products, and poor catalyst activity. Constructing reaction systems with different media, selecting and optimizing suitable catalysts to improve CO 2 The stability and efficiency of the reaction during the conversion process will be the key research direction in this field in the future.
[0004] However, in plasma conversion of CO 2In the process, there are still problems such as low energy efficiency of the reaction process. The addition of catalysts is conducive to the directional and efficient conversion of reactants. Combining plasma with catalytic technology can achieve the regulation and optimization of the reaction process.
[0005] According to previous research results and related reports, the selection and design of excellent catalysts are the key issues that plasma coupled catalytic technology aims to solve. The designed catalytic materials must first be able to fully match the characteristics of plasma, and secondly, they must adapt to the complex conditions of sintering flue gas and the characteristics of pollutants.
[0006] Since the plasma is rich in high-energy electrons, active free radicals and O 3 The design ideas of catalysts reported so far are mainly to improve the 3 From the perspectives of decomposition and utilization, increasing the surface active oxygen content of catalysts, and the influence of catalyst physical properties on plasma discharge morphology, there are still some problems such as high energy consumption and incomplete degradation. As high-energy electrons are the core species of plasma, there are still few catalysts that can effectively utilize high-energy electrons to improve plasma utilization and related mechanisms. Therefore, it is necessary to develop new catalysts that fully match the characteristics of plasma and explore their activation methods and the coupling mechanism between catalysts and plasma.
[0007] Studies have found that when metal-organic frameworks (MOFs) materials obtain a certain amount of energy, the conjugated π bonds will be extended, resulting in orbital delocalization, which can show the characteristics of semiconductors. The energy of high-energy electrons in low-temperature plasma can reach 1 to 20 eV, which can completely cover the energy required for semiconductor activation. Therefore, when high-energy electrons collide with catalysts, they can provide enough energy for the catalyst to activate it, generate new active free radicals to promote the degradation of pollutants; in addition, MOFs have a large specific surface area, and the research team has proved that they have excellent adsorption properties for chlorinated organic matter and mercury, which can effectively prolong their residence time in the discharge area and improve treatment efficiency. In addition to having good adsorption properties for pollutants, MOFs are also expected to form microporous discharges in plasma due to their unique porous characteristics, enhancing the discharge intensity, and will be a good choice for plasma catalytic systems.
[0008] Bismuth metal has good catalytic activity and is less toxic and harmless, so bismuth complexes are often used in green catalysts and are relatively cheap. Bi-MOFs are highly stable, reproducible, and have good catalytic activity. In addition to being used as catalysts, Bi-MOFs can be used in fluorescence due to its good chemical and thermal stability and the luminescent properties of its intrinsic ligands. Bismuth-based catalysts can reduce carbon dioxide to formic acid, carbon monoxide, methane, etc. under (photo) electrocatalytic conditions. It has also been shown to have good antibacterial properties and can be used in the fields of medicine and biology, but related research is not yet mature enough.
[0009] However, it is difficult to use catalysts to convert CO into 2 is completely reduced, resulting in CO 2 A mixture of Bi-MOF catalyst and quartz sand was filled into the discharge area of dielectric barrier discharge to construct an experimental system of low-temperature plasma coupled bismuth-based MOF catalyst for catalytic reduction of CO 2 To prepare CO, the active oxygen species generated by plasma can be used to increase the CO 2 The conversion rate can be increased by utilizing the properties of the catalyst to increase the CO yield and the energy density of the plasma. Summary of the invention
[0010] The present invention aims to solve the problems existing in the above-mentioned prior art and provide a low-temperature plasma coupled bismuth-based MOF catalyst for reducing CO 2 method.
[0011] The technical solutions adopted in the present invention are:
[0012] A low-temperature plasma coupled bismuth-based MOF catalyst for CO reduction 2 The method comprises the following steps:
[0013] 1) Preparation of Bi-MOF catalyst:
[0014] Dispersing 150 mg of bismuth nitrate pentahydrate and 750 mg of an organic ligand in 60 ml of an organic solvent, mixing by magnetic stirring to obtain an emulsion, placing the emulsion in a closed high-pressure reactor to react and obtain a mixture of solid and liquid, filtering the solid in the mixture and washing it with the organic solvent for multiple times to remove the residue on the surface of the solid, and placing the washed solid in an oven to dry to obtain a metal organic framework compound-Bi-MOF catalyst;
[0015] 2) Reduction of CO 2 :
[0016] The Bi-MOF catalyst and quartz sand prepared in step 1) are filled in the discharge area of the low-temperature plasma reactor, and then the gas-phase oxidant is introduced into the reactor at the gas inlet of the low-temperature plasma reactor; then, the discharge conditions of the dielectric barrier discharge of the low-temperature plasma reactor are adjusted to start discharge, so that the gas-phase oxidant catalytically reacts on the surface of the Bi-MOF and the quartz sand to generate CO, and the CO and other tail gases are discharged out of the reactor through the gas outlet of the low-temperature plasma reactor.
[0017] Further, in step 1):
[0018] The organic ligand is one of trimesic acid and terephthalic acid, or both trimesic acid and terephthalic acid are used;
[0019] The organic solvent is methanol or anhydrous methanol.
[0020] Furthermore, the gas phase oxidant is CO 2 , CO 2 Accounting for 95vt%-100vt% of the total gas volume in the low-temperature plasma reactor; CO 2 The total flow rate is 30ml / min.
[0021] Furthermore, the space velocity of the gas phase oxidant in the dielectric barrier discharge reaction zone of the low temperature plasma reactor is 50000-100000h -1 .
[0022] Further, in step 1): the magnetic stirring mixing time is at least 30 minutes;
[0023] The emulsion is placed in a sealed high-pressure reactor and reacted at 120° C. for 24 hours to obtain a mixture of solid and liquid;
[0024] The filtered solid was dried in an oven at 60-80°C for 1-5h.
[0025] Furthermore, the total mass of the Bi-MOF catalyst and quartz sand filled in the discharge region of the low-temperature plasma reactor is 4 g.
[0026] Furthermore, the low-temperature plasma reactor is a coaxial cylindrical DBD reactor, the discharge region length of the low-temperature plasma reactor is 50 mm, and the discharge power range is 20-60 W.
[0027] The present invention has the following beneficial effects:
[0028] 1) The present invention develops a new type of efficient and stable bismuth-based MOFs material that can fully utilize high-energy electrons in plasma through a reasonable process; on the one hand, the high-energy electrons in plasma are used to 2On the other hand, through the efficient catalytic materials, CO 2 removal efficiency and product CO yield.
[0029] 2) The present invention can overcome the thermodynamic reaction barriers at normal temperature and pressure and realize CO 2 It has strong reaction activity, fast reaction speed, low price, easy operation and good development prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The present invention is a low-temperature plasma coupled bismuth-based MOF to reduce CO 2 Schematic diagram of application (DBD synergistic catalysis);
[0031] Figure 2 The present invention is a method for reducing CO by low-temperature plasma in an empty pipe state. 2 Performance study diagram;
[0032] Figure 3 The present invention uses low-temperature plasma to reduce CO with quartz sand 2 Performance study diagram;
[0033] Figure 4 The low-temperature plasma of the present invention cooperates with 50 mg Bi-MOF catalyst and quartz sand mixture to reduce CO 2 Performance study diagram;
[0034] Figure 5 The present invention uses low-temperature plasma to synergize 100 mg Bi-MOF catalyst and quartz sand mixture to reduce CO 2 Performance study diagram;
[0035] Figure 6 The present invention uses low-temperature plasma to cooperate with 200 mg Bi-MOF catalyst and quartz sand mixture to reduce CO 2 Performance study diagram;
[0036] Figure 7 The low temperature plasma reduction of CO under five conditions of the present invention 2 Conversion rate comparison study chart;
[0037] Figure 8 The low temperature plasma reduction of CO under five conditions of the present invention 2 Energy efficiency comparison study chart;
[0038] Fig. 9 The low temperature plasma reduction of CO under five conditions of the present invention 2 Comparative study of CO selectivity. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the accompanying drawings.
[0040] The present invention discloses a low-temperature plasma coupled bismuth-based MOF catalyst for reducing CO 2 The method comprises the following steps:
[0041] 1) Preparation of Bi-MOF catalyst:
[0042] 150 mg of bismuth nitrate pentahydrate and 750 mg of organic ligand are dispersed in 60 ml of organic solvent, and an emulsion is obtained after magnetic stirring and mixing for at least 30 minutes. The emulsion is placed in a closed high-pressure reactor and reacted at 100-120° C. for 24 hours to obtain a mixture of solid and liquid. The solid in the mixture is filtered and washed 3 times with the organic solvent to remove the residue on the surface of the solid. The washed solid is placed in an oven at 60-80° C. and dried for 1-5 hours to obtain a metal organic framework compound - Bi-MOF catalyst.
[0043] The organic ligand in the present invention is one of trimesic acid and terephthalic acid, or both trimesic acid and terephthalic acid.
[0044] The organic solvent is methanol or anhydrous methanol.
[0045] 2) Reduction of CO 2 :
[0046] The Bi-MOF catalyst prepared in step 1) and quartz sand are filled in the discharge area of the low-temperature plasma reactor, and then a gas-phase oxidant is introduced into the reactor at the gas inlet of the low-temperature plasma reactor, wherein the gas-phase oxidant is CO 2 Subsequently, the discharge conditions of the dielectric barrier discharge of the low-temperature plasma reactor are adjusted to start discharge, so that the gas-phase oxidant undergoes a catalytic reaction on the surface of the Bi-MOF and the quartz sand to generate CO, and CO and other tail gases are discharged from the reactor through the gas outlet of the low-temperature plasma reactor.
[0047] The low-temperature plasma reactor in the present invention is a coaxial cylindrical DBD reactor, which has a stainless steel rod inserted into the inner tube as a high-voltage electrode, a quartz tube reactor as a dielectric tube, and a copper sheet as a ground electrode. The effective discharge area of the reactor is 50 mm, the unilateral discharge gap is 3 mm, and the discharge power range is 20-60 W.
[0048] Comparative Example 1
[0049] The reaction conditions are as follows: 95vt%-100vt% of gas phase oxidant CO is introduced into the low temperature plasma reactor. 2 , the total flow rate is 30ml / min, and the temperature in the catalyst chamber is 26℃.
[0050] The experimental steps are as follows: neither Bi-MOF catalyst nor quartz sand is filled in the low-temperature plasma reactor (i.e., an empty tube). 2 From the gas inlet Figure 1 In the dielectric barrier discharge reactor shown, a catalytic reaction is carried out in the discharge region of the reactor to produce CO, and CO and other tail gases are discharged through the gas outlet.
[0051] Conclusion: Under plasma reaction conditions, CO 2 The conversion reaction to CO, such as Figure 2 As shown, under the optimal conditions, the CO selectivity reached 78.93%, the CO yield reached 7.58%, the conversion rate reached 9.60%, and the energy efficiency was 1.35%.
[0052] Comparative Example 2:
[0053] The reaction conditions are as follows: 95vt%-100vt% of gas phase oxidant CO is introduced into the low temperature plasma reactor. 2 , the total flow rate is 30ml / min, and the temperature in the catalyst chamber is 26℃.
[0054] The experimental steps are as follows: first, fill the reactor with quartz sand, then 2 From the gas inlet Figure 1 In the dielectric barrier discharge reactor shown, a catalytic reaction is carried out in the discharge region of the reactor and on the surface of quartz sand to produce CO, and CO and other tail gases are discharged through the gas outlet.
[0055] Conclusion: Under the action of quartz sand alone and the above reaction conditions, the target product CO was generated. Figure 3 As shown, under the optimal conditions, the CO selectivity reached 81.48%, the CO yield reached 12.63%, the conversion rate reached 15.50%, and the energy efficiency was 2.17%.
[0056] Embodiment 1:
[0057] The difference from Comparative Example 2 is that 200 mg and 3800 mg of quartz sand are mixed and filled into the discharge area of the low-temperature plasma reactor.
[0058] The experimental steps are as follows: first, 200 mg of Bi-MOF catalyst and 3800 mg of quartz sand were mixed into a low-temperature plasma reactor, and CO 2 From the gas inlet Figure 1 In the dielectric barrier discharge reactor shown, a catalytic reaction is carried out in the discharge region of the reactor and on the surface of quartz sand to produce CO, and CO and other tail gases are discharged through the gas outlet.
[0059] Conclusion: After filling Bi-MOF catalyst in low temperature plasma reactor Figure 6 As shown, under the optimal conditions, the CO selectivity reached 68.85%, the CO yield reached 11.87%, the conversion rate reached 17.23%, and the energy efficiency was 2.49%.
[0060] like Figure 7-Figure 9 As shown, compared with Comparative Examples 1 and 2, Example 1 shows that under the optimal conditions, CO 2 The conversion rate and energy efficiency are both improved, and the CO yield is higher than that of Comparative Example 1 and slightly lower than that of Comparative Example 2.
[0061] Embodiment 2:
[0062] The difference from Example 1 is that the amount of Bi-MOF catalyst added is reduced, the reaction conditions and experimental steps are the same as the reaction conditions in Example 1, the amount of Bi-MOF catalyst in the discharge area is reduced to 100 mg, and the total amount of Bi-MOF catalyst mixed with quartz sand remains unchanged, i.e. 4 g.
[0063] The experimental results of Example 2 are as follows Figure 5 As shown in Figure 2, with the increase of discharge power, the CO selectivity and energy efficiency show a downward trend, but the amplitude is very small; CO 2 The conversion rate and CO yield increased; under the optimal conditions, CO 2 The conversion rate was 18.53%, the CO selectivity was 69.97%, the CO yield was 12.97%, and the energy efficiency was 2.68%.
[0064] Conclusion: Compared with Comparative Examples 1 and 2, Example 2 Figure 7-Figure 9 As shown, it shows that under the optimal conditions, CO yield, CO 2 The conversion rate and energy efficiency are improved. Figure 7-Figure 9 As shown in Figure 2, with the increase of discharge power, the CO yield and CO 2 The conversion rate and energy efficiency are both higher than those in Example 1.
[0065] Embodiment 3:
[0066] The difference from Examples 1 and 2 is that the amount of Bi-MOF catalyst added is further reduced; CO 2 The gases account for different volumes of the total gas.
[0067] The reaction conditions and experimental steps were the same as those in Examples 1 and 2, except that the amount of Bi-MOF catalyst in the discharge region was reduced to 50 mg, and the total amount of Bi-MOF catalyst mixed with quartz sand remained unchanged, i.e., 4 g.
[0068] The experimental results of Example 3 are as follows Figure 4 As shown in Figure 2, as the power increases, the energy efficiency decreases; CO 2 The conversion rate and CO yield increased. When the discharge power was 20W, the energy efficiency decreased significantly. Under the optimal conditions, CO 2 The conversion rate was 20.04%, the CO selectivity was 73.38%, the CO yield was 14.71%, and the energy efficiency was 3.44%.
[0069] Conclusion: Compared with Comparative Examples 1 and 2, Example 3 Figure 7-Figure 9 As shown, under the optimal conditions, CO yield and CO 2 The conversion rate and energy efficiency are improved. Compared with Example 1 and Example 2, Example 3 Figure 7-Figure 9 As shown in Figure 2, with the increase of discharge power, the CO yield and CO 2 The conversion rate and energy efficiency are higher than those of Example 1 and Example 2.
[0070] Table 1 shows the low temperature plasma reduction of CO under the optimal conditions of the present invention. 2 Performance comparison table.
[0071] CO2 conversion rate CO selectivity CO production rate Energy efficiency Comparative Example 1 9.60 78.93 7.58 1.35 Comparative Example 2 15.50 81.48 12.63 2.17 Example 1 17.23 68.85 11.87 2.49 Example 2 18.53 69.97 12.97 2.68 Example 3 20.04 73.38 14.71 3.44
[0072] Table 1
[0073] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements without departing from the principle of the present invention, and these improvements should also be regarded as within the protection scope of the present invention.
Claims
1. A method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst, characterized in that: The steps include: 1) Preparation of Bi-MOF catalyst: 150 mg of bismuth nitrate pentahydrate and 750 mg of an organic ligand are dispersed in 60 ml of an organic solvent, and an emulsion is obtained after mixing by magnetic stirring. The emulsion is placed in a closed high-pressure reactor to react and obtain a mixture of solid and liquid. The solid in the mixture is filtered and washed with the organic solvent for multiple times to remove the residue on the surface of the solid. The washed solid is placed in an oven to dry to obtain a metal organic framework compound-Bi-MOF catalyst; 2) Reduction of CO2: The Bi-MOF catalyst and quartz sand prepared in step 1) are filled in the discharge area of the low-temperature plasma reactor, and then the gas-phase oxidant is introduced into the reactor at the gas inlet of the low-temperature plasma reactor; then, the discharge conditions of the dielectric barrier discharge of the low-temperature plasma reactor are adjusted to start discharge, so that the gas-phase oxidant undergoes a catalytic reaction on the surface of the Bi-MOF and the quartz sand to generate CO, and the CO and other tail gases are discharged out of the reactor through the gas outlet of the low-temperature plasma reactor.
2. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 1, characterized in that: In step 1): The organic ligand is one of trimesic acid and terephthalic acid, or both trimesic acid and terephthalic acid. The organic solvent used was methanol.
3. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 1, characterized in that: The gas phase oxidant is CO2, and CO2 accounts for 95vt%-100vt% of the total gas volume in the low-temperature plasma reactor; the total flow rate of CO2 is 30ml / min.
4. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 3, characterized in that: The space velocity of the gas phase oxidant in the dielectric barrier discharge reaction zone of the low temperature plasma reactor is 50000-100000h -1 .
5. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 1, characterized in that: In step 1), the magnetic stirring mixing time is at least 30 minutes; The emulsion is placed in a sealed high-pressure reactor and reacted at 120° C. for 24 hours to obtain a mixture of solid and liquid; The filtered solid was dried in an oven at 60-80°C for 1-5h.
6. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 1, characterized in that: The total mass of the Bi-MOF catalyst and quartz sand filled in the discharge region of the low-temperature plasma reactor is 4 g.
7. The method for reducing CO2 using a low-temperature plasma coupled bismuth-based MOF catalyst as claimed in claim 1, characterized in that: The low-temperature plasma reactor is a coaxial cylindrical DBD reactor, the discharge area length of the low-temperature plasma reactor is 50 mm, and the discharge power range is 20-60 W.
Citation Information
Patent Citations
Preparation method of catalyst material for reducing CO2 into CO
CN112221497A
Bismuth-based metal organic framework material as well as preparation method and application thereof
CN112521618A